Становлення навчальних закладів із підготовки кадрів міліції в Харкові (1943–1990 рр.) - Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178 (Вісник Харківського національного університету внутрішніх справ. – 2014. – № 1 (64). – С. 29-39, 2014)
Розглянуто основні аспекти створення та функціонування спеціальних навчальних закладів, які займалися підготовкою та перепідготовкою кадрів міліції у Харкові протягом значного історичного періоду. The basic aspects of creation and functioning of different educational establishments, that prepared and engaged in retraining of shots of militia in Kharkiv, are investigated. This problem is unexplored. The training process of staff for police began immediately after the liberation of Kharkiv from the German Nazi occupation in 1943. Special training of police personnel after the war was conducted in three directions: in the system of permanent schools, police courses, through correspondence learning, extracurricular, in the form of commander training. Their distinguishing feature was that they were engaged in vocational study at the level of specific training or retraining. In this area it was accumulated considerable positive experience, trained a large number of police officers, formed a well trained teaching staff. All this has created the foundation for a new step in the development of police education – the creation of the Institute, and then – University of Internal Affairs. Рассмотрены основные аспекты создания и функционирования специальных учебных заведений, которые занимались подготовкой и переподготовкой кадров милиции в Харькове в течение значительного исторического периода.
Becoming of educational establishments from training of militia personnel in Kharkiv (1943–1990)
Становление учебных заведений по подготовке кадров милиции в Харькове (1943–1990 гг.)
Греченко, В. А. Становлення навчальних закладів із підготовки кадрів міліції в Харкові (1943–1990 рр.) / В. А. Греченко // Вісник Харківського національного університету внутрішніх справ. – 2014. – № 1 (64). – С. 29-39.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; органы внутренних дел; Internal Affairs Agencies; Історія. History. История; міліція; милиция; militia; підготовка кадрів; подготовка кадров; personnel training; спеціальні навчальні заклади; специальные учебные заведения; educational establishments; Харків; Харьков; Kharkiv